Impact after 10-year use of pneumococcal conjugate vaccine in the Brazilian national immunization program: an updated systematic literature review from 2015 to 2020. Issue 1 (31st December 2022) - Guzman-Holst, Adriana; de Barros, Eliana; Rubio, Pilar; DeAntonio, Rodrigo; Cintra, Otavio; Abreu, Ariane
ABSTRACT: In 2010, a 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) was introduced in the Brazilian national immunization program; the 3 + 1 dose schedule was replaced by a 2 + 1 dose schedule in 2016. This systematic review presents the latest published evidence (2015–2020) on the impact after 10-year use of PHiD-CV in Brazil from a total of 29 publications. Overall, the PHiD-CV program had a positive impact on the morbidity and mortality associated with invasive pneumococcal disease (IPD), pneumonia and acute otitis media (AOM) in children <5 years-old. A reduction in the vaccine-type invasive disease was observed in all-ages; suggesting indirect protection unvaccinated older children and adults. The occurrence of non-vaccine type disease was evidenced in some studies. Higher vaccination coverage is required at national and state level for sustained population impact. Given the change in the vaccination schedule and the dynamics of pneumococcal disease epidemiology, continuous surveillance is warranted. GSK Study identifier: HO-18-19438